2021
DOI: 10.3390/ph14060571
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Ginger and Its Constituent 6-Shogaol in Inhibiting Inflammatory Processes

Abstract: Ginger (Zingiber officinale Roscoe) is widely used as medicinal plant. According to the Committee on Herbal Medicinal Products (HMPC), dried powdered ginger rhizome can be applied for the prevention of nausea and vomiting in motion sickness (well-established use). Beyond this, a plethora of pre-clinical studies demonstrated anti-cancer, anti-oxidative, or anti-inflammatory actions. 6-Shogaol is formed from 6-gingerol by dehydration and represents one of the main bioactive principles in dried ginger rhizomes. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 63 publications
1
49
0
3
Order By: Relevance
“…Ginger is a well-known herbaceous plant and has long been used for relieving motion sickness, nausea, and abdominal pain [ 10 ]. It is known that ginger contains various bioactive compounds such as terpene, phenolic, and aromatic compounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginger is a well-known herbaceous plant and has long been used for relieving motion sickness, nausea, and abdominal pain [ 10 ]. It is known that ginger contains various bioactive compounds such as terpene, phenolic, and aromatic compounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that ginger contains various bioactive compounds such as terpene, phenolic, and aromatic compounds [ 11 ]. Among them, 6-shogaol is a main bioactive phenolic compound of dried ginger and exerts potent anti-oxidative and anti-inflammatory effects [ 10 ]. Previous studies have shown that an administration of 6-shogaol to rodents ameliorated various inflammatory diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-shogaol also demonstrated its anti-inflammatory effect to lower lung inflammation in a murine asthma model (Yocum et al, 2020), protect against acute lung injury in mice (Wang et al, 2016), downregulate inflammatory markers in hamster buccal pouch carcinogenesis (Annamalai & Suresh, 2018), inhibit monosodium urate crystalinduced inflammation in mice (Sabina et al, 2010), and reduce neuroinflammation in rodent models of dementia (Moon et al, 2014). A recent review of 30 in vivo and in vitro studies further confirmed 6-shogaol to be a promising antiinflammatory substance, but conclusive clinical data remained lacking (Bischoff-Kont & Fürst, 2021). Nevertheless, it is reasonable to assume that 6-shogaol can potentially reduce chronic Is 6-Shogaol a beneficial phytochemical for patients with lower-risk myelodysplastic syndrome?…”
Section: Therapeutic Propertiesmentioning
confidence: 99%
“…We noticed that enteric bacteria could quickly uptake exosomal lipid nanoparticles (eLNP) derived from ginger [ 13 ], and 6-shogaol (6S)-containing ginger juice had substantial effects on the change of composition and function of gut microbiota in healthy people (after seven days of treatment) [ 14 ]. 6S is one of the major active compounds of ginger and is proven to have excellent antioxidative, anti-inflammatory, and anticarcinogenic properties [ 15 , 16 , 17 ]; also, poly-lactic acid nanoparticles (PLA-NPs)-delivered 6S has shown superior therapeutic efficacy against UC [ 18 ]. As our preliminary data indicated that 6S presented an effect on gut microbiota composition change with the potential of gradually increasing the F/B ratio, we hypothesized that 6S delivered by reassembled LNP from ginger lipids (6S/nLNP) could be readily uptaken by the enteric bacteria, and the natural LNP (nLNP) encapsulation might reduce the time required for the onset of action of 6S on compositional change of microbiota.…”
Section: Introductionmentioning
confidence: 99%